2017
DOI: 10.1371/journal.pone.0189319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusobacterium varium Fv113-g1 isolated from a patient with ulcerative colitis based on complete genome sequence and transcriptome analysis

Abstract: Fusobacterium spp. present in the oral and gut flora is carcinogenic and is associated with the risk of pancreatic and colorectal cancers. Fusobacterium spp. is also implicated in a broad spectrum of human pathologies, including Crohn’s disease and ulcerative colitis (UC). Here we report the complete genome sequence of Fusobacterium varium Fv113-g1 (genome size, 3.96 Mb) isolated from a patient with UC. Comparative genome analyses totally suggested that Fv113-g1 is basically assigned as F. varium, in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…nucleatum , F . varium [9] has also recently gained notoriety as a gastrointestinal pathogen [10, 11]. Indeed, links between the enrichment of Fusobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…nucleatum , F . varium [9] has also recently gained notoriety as a gastrointestinal pathogen [10, 11]. Indeed, links between the enrichment of Fusobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota surveys in Japanese cohorts have indicated that F. varium is associated with UC, 21 22 and a genome sequencing study of F. varium strain Fv113-g1 isolated from a UC patient reported expression of FadA homologues in monocultures simulating in vivo conditions within the human gut. 68 Our data on FadA homologues show that sequences from the Fusobacterium _A clade ( F. varium , F. ulcerans and other uncharacterised sister taxa) are not identical to sequences from the Fusobacterium clade (in which the CRC-associated F. nucleatum is located) ( figure 4 ), thereby suggesting distinct functions or targets among these homologues. While the presence/absence of these gene homologues do not directly translate to invasiveness, 69 we postulate that Fusobacterium _A taxa and their copies of the FadA homologue can be risk factors for diseases other than CRC.…”
Section: Discussionmentioning
confidence: 85%
“…As for F. varium and F. ulcerans , less is known about their distribution and association with cancers or disease. Gut microbiota surveys in Japanese cohorts have indicated that F. varium is associated with UC,21 22 and a genome sequencing study of F. varium strain Fv113-g1 isolated from a UC patient reported expression of FadA homologues in monocultures simulating in vivo conditions within the human gut 68. Our data on FadA homologues show that sequences from the Fusobacterium _A clade ( F. varium , F. ulcerans and other uncharacterised sister taxa) are not identical to sequences from the Fusobacterium clade (in which the CRC-associated F. nucleatum is located) (figure 4), thereby suggesting distinct functions or targets among these homologues.…”
Section: Discussionmentioning
confidence: 99%
“…(one OTU) and Veillonella dispar (one OTU). Specific species of Fusobacterium, such as F. nucleatum and F. varium, were reported to be associated with the promotion of intestinal inflammation 18,19 . The population of V. dispar was shown to be significantly larger in patients with severe disease compared to those with mild disease in a large-scale study of gut bacterial communities affected by IBD 20 .…”
Section: Discussionmentioning
confidence: 99%